Antiproliferative Effect and Cell Cycle Alterations Induced by Salvia officinalis Essential Oil and Its Three Main Components in Human Colon Cancer Cell Lines. Issue 8 (27th July 2020) - Luca, Tonia; Napoli, Edoardo; Privitera, Giovanna; Musso, Nicolò; Ruberto, Giuseppe; Castorina, Sergio
Abstract: Colon cancer is one of the most common human malignancies, and chemotherapy cannot yet prevent recurrence in all patients. Essential oils are phytocomplexes with antiproliferative properties. In this study, we elucidated the antiproliferative properties and the effect on cell cycle progression of Sicilian Salvia officinalis essential oil and its three main compounds, α ‐thujone, 1, 8‐cineole (eucalyptol) and camphor, on three human colon cancer cell lines. The essential oil was obtained by hydrodistillation and analyzed by gas chromatography. Cell proliferation was evaluated by MTT assay, and the cell cycle distribution was determined by flow cytometry. Thirty‐four compounds were identified in the tested essential oil. Growth inhibition was observed after 72 h, with an impact on cell cycle progression and no effect on the viability of normal colonic epithelial cells. The study shows that S. officinalis essential oil and its three main components have an in vitro antiproliferative effect on colon cancer cells. Abstract :